Penggunaan Aplikasi Zahir Accounting untuk Penyusunan Laporan Keuangan pada CV Wira Bone - Raudatul Janah; Yuli Fitriani; Karolina (Indonesian Journal of Applied Accounting and Finance, 2021)
Financial statements are usually prepared by the company for activities that have occurred for transactions. Likewise, CV Wira Bone, which is a CV or a company engaged in a welding workshop. Previously, this CV did not have financial statements, only simple evidence of transactions and financial records. So, in knowing the benefits, mistakes can still occur and making decisions will be difficult because you do not know the company's financial performance. So in this case it is necessary to prepare financial reports to provide information about the company's financial records. The compilation of financial reports can be done using a computerized system using the Zahir Accounting Version 6. The data obtained is in the form of financial data that is owned by the company which is requested directly and its suitability with the company's activities that have occurred. With the Zahir application, the resulting financial reports are more accurate, effective and efficient so that they can find out the company's financial performance for making future decisions. The use of Zahir Accounting Version 6 is a good solution for solving problems that occur regarding company finances because it can provide convenience for the company itself. So using this computerized system will be better than using a manual system because it can provide convenience, the results obtained are accurate, effective, efficient and can minimize the time used